1993
DOI: 10.1038/ng0693-170
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of an autosomal sex reversa– locus (SRA1) and campomelic dysplasia (CMPD1) to 17q24.3–q25.1

Abstract: We have mapped the autosomal sex reversal locus, SRA1, associated with campomelic dysplasia (CMPD1) to 17q24.3-q25.1 by three independent apparently balanced de novo reciprocal translocations. Chromosome painting indicates that the translocated segment of 17q involves about 15% of chromosome 17 in all three translocations, corresponding to a breakpoint at the interphase between 17q24-q25. All three 17q breakpoints were localized distal to the growth hormone locus (GH), and proximal to thymidine kinase (TK1). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
4

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(82 citation statements)
references
References 33 publications
1
77
0
4
Order By: Relevance
“…(1) Sox2 binds the same DNA sequences recognized by Fx; (2) The functional ability of Sox2 to trans-activate the FGF-4 enhancer is clearly demonstrated by cotransfection as says using HeLa cells; (3) Antiserum (aHSox2) raised against the HMG domain of Sox2 also recognizes Fx, establishing that Fx is a Sox factor; (4) aHSox2 antiserum immunoprecipitates what is apparently a single protein from F9 nuclear extracts that corresponds in molecular mass (35 kD) to that predicted by the cDNA sequence of Sox2 (which suggests that only one Sox factor is present in F9 nuclear extracts and/or only this one species is recognized by aHSox2); (5) Sox2 protein-DNA com plexes exhibit the same mobility as Fx-DNA complexes in nondenaturing gels, suggesting that the molecular mass of Fx corresponds to that of Sox2. Although it is formally possible that Fx represents an additional 35-kD Sox factor present in F9 nuclear extracts, this is not the published molecular mass of murine Sox4, Sox5, and Sox9 and human Sox9 or chicken Soxll (Denny et al 1992;van DeWetering et al 1993;Tommerup et al 1993;Wright et al 1993Wright et al , 1995Uwanogho et al 1995). One exception might be Sox3 because the recently pub lished chicken Sox3 cDNA sequence encodes a protein of 315 amino acids (Uwanogho et al 1995).…”
Section: Genes and Developmentmentioning
confidence: 70%
See 1 more Smart Citation
“…(1) Sox2 binds the same DNA sequences recognized by Fx; (2) The functional ability of Sox2 to trans-activate the FGF-4 enhancer is clearly demonstrated by cotransfection as says using HeLa cells; (3) Antiserum (aHSox2) raised against the HMG domain of Sox2 also recognizes Fx, establishing that Fx is a Sox factor; (4) aHSox2 antiserum immunoprecipitates what is apparently a single protein from F9 nuclear extracts that corresponds in molecular mass (35 kD) to that predicted by the cDNA sequence of Sox2 (which suggests that only one Sox factor is present in F9 nuclear extracts and/or only this one species is recognized by aHSox2); (5) Sox2 protein-DNA com plexes exhibit the same mobility as Fx-DNA complexes in nondenaturing gels, suggesting that the molecular mass of Fx corresponds to that of Sox2. Although it is formally possible that Fx represents an additional 35-kD Sox factor present in F9 nuclear extracts, this is not the published molecular mass of murine Sox4, Sox5, and Sox9 and human Sox9 or chicken Soxll (Denny et al 1992;van DeWetering et al 1993;Tommerup et al 1993;Wright et al 1993Wright et al , 1995Uwanogho et al 1995). One exception might be Sox3 because the recently pub lished chicken Sox3 cDNA sequence encodes a protein of 315 amino acids (Uwanogho et al 1995).…”
Section: Genes and Developmentmentioning
confidence: 70%
“…Mutations within certain Sox factor genes have been found to underlie several developmental abnormal ities including sex reversal, campomelic dysplasia, and Borjeson-Forssman-Lehmann syndrome, suggesting that Sox factors play an essential role in the execution of specific developmental programs (Gubbay et al 1990;Sinclair et al 1990;Stevanovic et al 1993;Tommerup et al 1993;Wright et al 1993;Foster et al 1994;Wagner et al 1994). However, none of the target genes regulated by Sox factors have been identified to date.…”
mentioning
confidence: 99%
“…21 In the present study we have found 441 instances of such a cooccurrence, but since this includes common disorders, their significance varies. On the list of the six combinations with the highest LLR-values (Table 3) we found cervical dysplasia and 11q23 where the presence of a cervixassociated tumour suppressor gene has been suggested due to the frequent observation of loss of heterozygozity for 11q23 in cervical tumour tissues.…”
Section: Bache Et Almentioning
confidence: 87%
“…Chegou-se, posteriormente, à conclusão de que mutações no gene SOX9, localizado nessa mesma região, eram responsáveis pela Displasia Camptomélica. Uma vez que essas mutações, encontradas em apenas um dos alelos, levam, na prática, à inativação do gene, conclui-se que a Displasia Camptomélica seja resultante de haploinsuficiência do gene SOX9 (25)(26)(27).…”
Section: Disgenesias Gonadais E Tumoresunclassified